An Analysis on Speech Styles Used by English Lecturers - Evi Riasari; Syarifuddin Dollah; Kisman Salija (Har Press Indonesia, 2021)
The objectives of this research were to (1) find out the types of speech styles used by English lecturers in teaching-learning process and (2) explore the impact of lecturers’ speech style on the students’ attitude towards the lesson. The method of this research was a qualitative descriptive research. There were 2 lecturers and 30 students of 4th semester as the participants of this research. The data were obtained through observation checklist, interview, and video/audio recording. The data from audio recording were transcribed into written form to be analyzed. The result of this research showed that there were 4 speech styles were used by the English lecturer such as formal style, consultative style, casual style, and intimate style. The lecturers used 2 to 4 speech style in teaching-learning process. The impact of lecturer speech style on the students’ attitude towards the lesson, based on the result of the observation and the interview with the students, can be concluded: first, the use of formal speech style did not make the students participate actively and enthusiastically in the lesson even though some students feel that the use of formal style in teaching-learning process could give them more lesson on the language and some feel it is easier to understand the lesson. It is because they felt anxious about the grammatical error that may occur when they speak. Second, the use of consultative style motivated the students to learn more because they felt challenging when the teacher asked them their prior knowledge or opinion regarding the lesson material. The students also participate actively in the class discussion because they think when their lecturers ask them questions; their lecturer is testing their knowledge and ability. It is also stimulated by the belief about effective students is the one who participate actively in the class. Third, the students participate actively and enthusiastically when the lecturer used casual speech style because they do not have to be anxious of the grammar when they speak. The students feel relax and comfortable because the language that is used by the lecturer is the language that they used every day. Fourth, the use of intimate speech style got the students participate actively in the class and got more interested in the lesson. This speech style made the students felt relax and comfortable in the lesson because they felt a close lecturer-students relationship.